The effectiveness of holistic marketing as a survival tactic in a crisis economy: a case of the Zimbabwe Newspapers Group 1980 ltd Sales and Marketing Department. - Chikadaya, Lesley L (Midlands State University, 2018)
The study seeks to provide a solution on how media organizations can employ marketing strategies to survive the economic. With the advent of new trends in the global marketing world, this study explored the implementation of the holistic marketing concept and its effectiveness in a crisis ridden Zimbabwean economy by Zimbabwe Newspapers (1980) Ltd. It addresses the gap on how print media organizations can best utilize marketing to stay viable in an unstable economic environment. The continued crisis is posing serious challenges on media organizations’ operations and these have put marketing departments in the spotlight as they are expected to come up with innovative ways to counter the prevailing situation. In an attempt to fully understand the phenomenon, the study takes on an exploratory approach and is guided by the holistic marketing concept and marketing mix theories. Relevant data was gathered through structured interviews, participant and nonparticipant observation as well as through archival research in order to obtain the most accurate data which fully addressed the topic study. This was then tabulated for interpretation and analysis. Findings suggested that the implementation of the Holistic Marketing concept combined with the most appropriate modifications of the marketing mix boosted revenues resulting in Zimpapers’ recording a good financial year making it crucial for other media organizations to adopt the strategy. Further research may be done by critically examining each of the components of holistic marketing namely relationship marketing, internal marketing, socially responsible marketing and integrated marketing communications from a digital perspective.